Determination of Pediatric Patient Companion Dose at Thoracic X-Ray Examination - Ega Duandini; Eko Hidayanto; Wahyu Setia Budi (Journal of Physics and Its Applications, 2022)
Thorax radiography examination in pediatric patients is one of the most frequent examinations because of many abnormalities that occur in the thorax and have a high probability at children's age. Pediatric patients are assisted by a companion from the adult patient's family. Calculation and measurement of the radiation dose received by the companion are very important as they are in the examination room with the patient during the imaging process. And no matter how small the radiation dose received by the companion, there will be an opportunity for stochastic effect. The Indonesian Nuclear Energy Regulatory Agency regulation Number 4 of the Year 2020 on Radiation Safety in the Use of X-Ray Machines in Diagnostic and Interventional Radiology, regulates the dose received by patient companions must be less than 5 mSv. This study aims to analyze the relationship between the exposure factor and the radiation dose received by the patient's companion. The TLDs used to measure the radiation dose was placed on the companion's chest. The radiation dose was calculated using the Klein-Nishina formula. The results show that the dose received by the companion ranged from 0.39 × 10-5 mSv to 4.64 × 10-5 mSv, which is much lower than the permissible dose.